Biotechnology Explorations applying the Fundamentals - Scheppler, Judith A Cassin, Patricia E (ASM Press, 2000)
This exciting volume offers a broad collection of college-level experiments that provides students with a hands -on-understanding of biotechnology and molecular biology, including applications and practical uses. Each investigation includes suggested reading, laboratory language, and analysis questions that help direct student thinking. Sidebar comments offer special hints and detailed information to ensure success but keep the protocols themselves easy to follow. Comprehensive laboratory safety guidelines are also included. The experiments, organized into fundamental laboratory activities and applications of these protocols, can be adapted to fit the time frame of a one-or-two-semester laboratory course.